Comparative Analysis of L‐Dopa and Deep Brain Stimulation on Bradykinesia Components in Parkinson's Disease - Daniel S. Marín‐Medina; Miguel Wilken; Florencia Wainberg; Marcelo Merello (Movement Disorders Clinical Practice, 2026)
Abstract Background Parkinson's disease (PD) bradykinesia is a complex of motor abnormalities. Subthalamic Nucleus Deep Brain Stimulation (STN‐DBS) and L‐dopa both improve bradykinesia, but their differential effects on each component remain unknown. Objective To quantify and compare the differential effects of STN‐DBS and L‐dopa on the individual kinematic components of bradykinesia. Methods PD patients with bilateral STN‐DBS were prospectively evaluated at least 3 months after surgery. Clinical and kinematic analyses of finger tapping were performed under three conditions: OFF, ON‐DBS (clinically optimized stimulation), and ON‐medication. Bradykinesia was decomposed into amplitude, velocity, dysrhythmia, sequence effect, hesitations, and interruptions. Data were analyzed using repeated‐measures ANOVA or Friedman tests, with adjusted post‐hoc comparisons. Results Twenty patients with PD were evaluated: median follow‐up after surgery of 9.5 [3.75–11.5] months. Both L‐dopa and STN‐DBS significantly improved clinical MDS‐UPDRS finger‐tapping scores compared to baseline ( P < 0.001). STN‐DBS showed a significantly greater effect on interruptions ( P = 0.03), while L‐dopa only showed a greater effect on hesitations ( P = 0.03), compared with the OFF baseline. Dysrhythmia and sequence effect were unaffected by either therapy. When several features of bradykinesia were combined in a composite kinematic score, both therapies showed a significant difference compared with the OFF baseline ( P < 0.01). Conclusions Despite comparable clinical efficacy, L‐dopa and STN‐DBS have different profiles of kinematic effects on the components of bradykinesia implicated in motor blocks. Understanding these distinctions is essential for refining motor assessments and developing therapies targeting specific pathophysiological mechanisms.